Awareness of medico-legal issues among medical and dental college health professionals - S Senthilkumar; V Chandrasekhara Reddy; Navin Anand Ingle (Wolters Kluwer Medknow Publications, 2013)
Introduction: The changing doctor-patient relationship and commercialization of modem medical practice has affected the practice of medicine. The fundamental values of medicine insist that the doctors should be aware about the various medico-legal issues which help in proper recording of medical management details. Aim: To evaluate the knowledge on Medico-legal Issues among Medical and Dental College Health Professionals of Meenakshi University (MAHER), Tamilnadu. Materials & Method: A cross-sectional survey was conducted among health professionals of Meenakshi University (MAHER), Tamilnadu. A total o f320 health professionals (163 medical and 157 dental) participated in the study. A structured, closed ended, self-administered questionnaire was used for collection of data. Chi-square test was used to compare the awareness of medico-legal issues between medical and dental health professionals. Results: Among the 320 health professionals, 87.4% of medical and 76.1% of dental professionals were aware about the informed consent, 18.8% of medical and 5.7% of dental professionals had awareness about COPRA and only 14.3% of medical and 7.6% of dental professionals had awareness regarding the Medico-legal programs/courses. Conclusions: The results illustrated that the participants had little awareness on medico-legal issues. Hence there is an urgent need to update the understanding of these issues to be on a legally safer side.